The Epigenetic Role of MiRNAs in Endocrine Crosstalk Between the Cardiovascular System and Adipose Tissue: A Bidirectional View - Soci, Ursula Paula Reno; Cavalcante, Bruno Raphael Ribeiro; Improta-Caria, Alex Cleber; Roever, Leonardo (Frontiers in Cell and Developmental Biology, 2022)
Abstract Overweight and obesity (OBT) is a serious health condition worldwide, and one of the major risk factors for cardiovascular disease (CVD), the main reason for morbidity and mortality worldwide. OBT is the proportional increase of AT (AT) compared with other tissue and fluids, associated with pathological changes in metabolism, hemodynamic overload, cytokine secretion, systemic inflammatory profile, and cardiac metabolism. In turn, AT is heterogeneous in location, and displays secretory capacity, lipolytic activation, insulin sensitivity, and metabolic status, performing anatomic, metabolic, and endocrine functions. Evidence has emerged on the bidirectional crosstalk exerted by miRNAs as regulators between the heart and AT on metabolism and health conditions. Here, we discuss the bidirectional endocrine role of miRNAs between heart and AT, rescuing extracellular vesicles' role in cell-to-cell communication, and the most recent results that show the potential of common therapeutic targets through the elucidation of parallel and ⁄or common epigenetic mechanisms.